BUDAYA SEKOLAH, MOTIVASI KERJA, KOMITMEN TUGAS SEBAGAI FAKTOR DETERMINAN DALAM MEMPENGARUHI KINERJA KEPALA SMP KABUPATEN PESISIR SELATAN - man, Yar (Menara Ilmu, 2018)
The aim of this study was to determine the direct and indirect relationships betweenexogenous variables on endogenous between school’s culture, employee’s motivation andcommitment to the performance of the principal’s tasks. The background of this studybegins with the discovery of a variety issues regarding the performance of the junior highschool’s principal in Pesisir Selatan that the problem is dominated by the culture ofschool, work motivation, and commitment to the task.This research belongs to quantitative through path analysis approach. Populationin this research is 70 principals of junior high school in Pesisir Selatan. The samples inthis study were selected by using random sampling techniques. Samples obtained from therandomization are 59. Data were collected through questionnaires and analyzed usinganalysis Product Moment analysis by using SPSS version 16.Findings prove that: (1) there is influence of culture (X1) on the performance ofschool’s principals (Y) by 75.8%; (2) there is influence of work motivation (X2) on theperformance of school’s principals (Y) by 51.9%; (3) there is influence of task commitment(X3) on the performance of school’s principals (Y) by 49.5%; (4) there is a direct effect ofschool’s culture (X1) to task commitment (X3) by 37.7%; (5) there is a direct effect of workmotivation (X2) to task commitment (X3) by 8.79%; (6) there is no direct effect of school’sculture (X1) of the principal’s performance (Y) via the task commitment (X3) by 37.16 %;and (7) there is no direct effect of work motivation (X2) on the performance of school’sprincipals (Y) via the task commitment (X3) by 44.6%.Keywords: School’s Culture, Work Motivation, Task Commitment, Principal’sPerformance.